THE AUTOMATIC BLOOD PRESSURE METER FOR RESEARCH PURPOSES USING DIGITAL FILTRATION - R. M. Kishov (Вестник Дагестанского государственного технического университета: Технические науки)
Аrterial hypertension and its consequences such as ischemic stroke and cardiac infarction are remains ones of the most lethal and at the same time prevailing at the same human’s diseases. Necessity of constant instrumental blood pressure monitoring is one of the inalienable parts of the such diseases’ prevention and therapy. In this article digital blood pressure meter for research purposes using digital filtration is proposed.